Quality of Spring Water in the Catchment Areas of the Indus River - ASLAM MIRZA, M.; KHUHAWAR, M.Y.; ARAIN, RAFEE (Asian Journal of Chemistry, 2010)
A systematic and detailed study of the quality of spring water was conducted to assay the influence of rainfall, snow melt, deforestation, urban sewage and per se geochemical interactions. The area covered is at the foothills of Himalayas forming predominantly the catchments area of Indus river. 30 Springs were sampled over a period of two years on seasonal and hydrological cycle basis. The preliminary results indicate TDS for half of the water samples within 115- 499 mg/L, for the remaining half it exceeds 500 mg/L. Inter sample, seasonal and hydrological cycle variance indicate no significant change in elemental composition and organic matter content but those contaminated with sewage of deforested locations show substantial variation both in elemental and organic matter content. Low rainfall also deters the dilution of pollutants occurring both naturally and through human activity. This study provides the database of the quality of water of Indus river.